The Significance of Principal Management on Teacher Performance and Quality of Learning - Deti Rostini; Rifqi Zaeni Achmad Syam; Willya Achmad (STAI Hubbulwathan Duri, 2022)
Improving the quality of learning can be achieved by the quality of managerial ability of the principal who is creative and innovative in managing the school. When the principal's managerial implementation has not been optimal in carrying out the main tasks and functions, it has an impact on the weak performance of teachers. Therefore, the principal has the task and role of providing guidance to improve teacher performance and the quality of learning. Based on these problems, the purpose of this research is to obtain an overview of how the planning, organizing, implementation and evaluation of school principals in improving teacher performance and learning quality. The research method used is documentation studies from relevant literature. Eight articles were used as the data. The results showed that: 1) school principals always plan teacher performance coaching programs, make methods and forms of performance coaching, allocate performance coaching time, 2) organize performance coaching including: a clear organizational structure, division of labor, 3) on the implementation function. generally carried out at the beginning of the school year and at the beginning of each semester, the routine implementation every month the principal always provides performance guidance, 4) at the evaluation stage held at the end of each semester, and also conducts class visits, the results achieved. This study concludes that the principal management has contributed positively towards the teacher performance and improved the quality of learning.